THE INFLUENCE OF USING E-LEARNING AND SELF-EFFICACY ON STUDENTS' LEARNING ACHIEVEMENT IN THE COVID-19 PANDEMIC - Sutirman, Sutirman; Prasetiyadi, Nathaniela Oci; Solikhah, Mar'atus (Departemen Pendidikan Administrasi FEB Universitas Negeri Yogyakarta & ASPAPI PUSAT, 2024)
Abstrak: The Influence of Using E-Learning And Self-Efficacy on Students' Learning Achievement In The Covid-19 Pandemic.Pandemi Covid-19 mendorong semua sekolah di Indonesia melaksanakan pembelajaran secara online. Penelitian ini bertujuan untuk mengetahui pengaruh: 1) penggunaan e-learning terhadap prestasi belajar siswa pada masa pandemic covid-19; 2) self efficacy terhadap prestasi belajar siswa pada masa pandemic covid-19; 3) penggunaan e-learning dan self efficacy terhadap prestasi belajar siswa pada masa pandemic covid-19. Penelitian ini merupakan penelitian asosiatif kausal menggunakan desain ex post facto dengan pendekatan kuantitatif. Populasi penelitian ini adalah siswa kelas X program studi Otomatisasi dan Tata Kelola Perkantoran SMK Negeri 1 Pengasih sejumlah 72 siswa. Analisis data penelitian menggunakan teknik analisis regresi sederhana dan regresi ganda. Hasil penelitian menunjukkan bahwa: 1) terdapat pengaruh positif dan signifikan penggunaan e-learning terhadap prestasi belajar siswa pada masa pandemi covid-19 sebesar 33,3%; 2) terdapat pengaruh positif dan signifikan efikasi diri terhadap prestasi belajar siswa pada masa pandemi covid-19 sebesar 37,8%; 3) terdapat pengaruh positif dan signifikan penggunaan e-learning dan efikasi diri secara simultan terhadap prestasi belajar siswa pada masa pandemi Covid-19 sebesar 40,4%. Kata kunci: E-learning; Pandemi covid-19; Prestasi belajar; Self efficacy Abstract: The Influence of Using E-Learning And Self-Efficacy on Students' Learning Achievement In The Covid-19 Pandemic. The Covid-19 pandemic has pushed all schools in Indonesia to carry out online learning. This study aims to determine the effect of 1) the use of e-learning on student achievement during the co-19 pandemic; 2) self-efficacy for student learning achievement during the Covid-19 pandemic; 3) the use of e-learning and self-efficacy on student achievement during the co-19 pandemic. This research conducted with causal associative research using ex post facto design with a quantitative approach. The population of this research was class X students of the Automation and Office Management study program at SMK Negeri 1 Pengasih with a total of 72 students. Analysis of research data using simple regression analysis techniques and multiple regression. The results of the study showed that: 1) there was a positive and significant effect of the use of e-learning on student achievement during the Covid-19 pandemic by 33.3%; 2) there was a positive and significant effect of self-efficacy on student achievement during the Covid-19 pandemic of 37.8%; 3) there was a positive and significant effect of the use of e-learning and self-efficacy simultaneously on student achievement during the Covid-19 pandemic of 40.4%.Keyword: E-learning; Covid-19 pandemic; Learning achievement; Self efficacy